Reconstructing The Regulatory Framework of Stock Waqf In Indonesia’s Sharia Capital Market: Institutional And Sustainability Perspectives - Paisal Rahmat; Ilham Putra Usmayani; Syamratun Nurjannah; Haris Maiza Putra; Jureid Jureid (Universitas Muhammadiyah Bandung, 2026)
The institutional framework and sustainability of waqf in Indonesia hold immense potential for supporting the social and economic development of the Muslim community. However, despite its promise, the sector remains fragmented, and its utilization has not yet been optimized due to the lack of specific legal regulations governing stock waqf. This study analyzes the regulatory framework for stock waqf from the perspectives of institutionalization and sustainability in Indonesia. Employing a qualitative method through normative legal research using a conceptual approach, this study examines the reconstruction of stock waqf from the perspectives of institutionalization and sustainability in Indonesia. The research findings emphasize the need for legal reconstruction regarding the institutional framework and sustainability of stock waqf to integrate collaborative legal regulations among the Indonesia Stock Exchange, the Financial Services Authority, and the Indonesian Waqf Board, as well as to strengthen Islamic financial literacy. Collaborative legal regulation is not only necessary for operational effectiveness but also to integrate waqf into a modern economic framework, including the integration of digital governance systems and the strengthening of electronic nazhir certification systems without compromising their ethical foundations. Recommendations include strengthening specific legal regulations for stock waqf, fostering synergy between the government and religious authorities, and implementing collaborative legal integration among the Indonesia Stock Exchange, the Financial Services Authority, and the Indonesian Waqf Board. These findings contribute to the reconstruction of the endowment system from an institutional perspective and to the sustainability of endowments that are responsive to national socioeconomic needs and the needs of the endowment itself.